PERAN KETEBALAN TUNIKA INTIMA MEDIA KAROTIS TERHADAP FUNGSI KOGNITIF PADA WANITA MENOPAUSE - Mulia Rahmansyah; Nany Hairunisa; Yudhisman Imran; Pramesti Indri Miranti; Irmiya Rachmiyani; Cylla Revata (NEURONA, 2022)
Menopause is one of the most important physiological stages in a woman's life; it is a complex process involving the endocrine system and regulating neurological functions. Increasing age is associated with decreased cognitive function. Low estrogen levels after menopause accelerate the process of cognitive decline, and Estrogen plays an important role in vasodilating and anti-inflammatory functions and plays a protective function in the prevalence of Coronary Artery Disease (CAD). Subclinical atherosclerosis is a potential risk factor for impaired cognitive function and dementia in the elderly. The decrease in cerebral blood flow (CBF) due to turbulence that occurs in the sclerotic area and accelerated brain atrophy due to reduced blood supply is evidenced by the results of research that patients who do not clinically show cerebrovascular disease can experience decreased cognitive function due to severe stenosis of the carotid arteries. Assessment of carotid intimal–medial thickness (cIMT) is a non-invasive test to measure atherosclerosis and is widely used to screen for risk factors for cerebrovascular disease. CIMT was measured using ultrasound as a marker of atherosclerosis. CIMT can directly provide an image of blood vessels, allowing for assessing atherosclerosis rather than vessel lumen. Decreased cognitive function has a significant relationship with carotid artery stenosis so CIMT can be used as a predictor of cognitive decline in the elderly, especially in postmenopausal women. Various existing studies confirm a significant relationship between cIMT thickening and cognitive decline. Keywords :Carotid Intima – Media Thickness (CIMT), Cognitive Function, Menopause